2020
DOI: 10.1155/2020/8695783
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Occupational Stress and Its Relationship with Secretory Immunoglobulin A in the Xinjiang Plateau Young Military Recruits

Abstract: Background. With the continuous improvement of the modernization of the Chinese military and the major adjustments made by the state to the recruitment policy, the newly recruited military undergone multiple pressures such as targeted high-intensity military training and environmental changes. The mental health of military has become a crucial factor of improving the fighting capacity effectiveness of the troops. Objectives. To explore occupational stress of young recruits in the Xinjiang plateau environment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Previous research has suggested that acute stress caused by environmental changes can result in an increase in s-IgA synthesis as an adaptive response by the body. 65 One study reported that the increase in s-IgA concentration occurred within the first 15 minutes of acute stress and was reduced to baseline levels, thereafter; although salivary cortisol levels increased and were mainatained due to continued stress. 54 In our study, acute stress might occur during the first saliva collection during adaptation to a new environment, whilst the levels of salivary cortisol may not increase in the absence of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that acute stress caused by environmental changes can result in an increase in s-IgA synthesis as an adaptive response by the body. 65 One study reported that the increase in s-IgA concentration occurred within the first 15 minutes of acute stress and was reduced to baseline levels, thereafter; although salivary cortisol levels increased and were mainatained due to continued stress. 54 In our study, acute stress might occur during the first saliva collection during adaptation to a new environment, whilst the levels of salivary cortisol may not increase in the absence of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Under such circumstances, the choice of their coping style is related to the army's combat effectiveness, especially in psychological warfare plays a decisive and dominant role. Therefore, efforts to improve their psychological stress coping ability and coping style selection can help improve military mission execution effectiveness (Tao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al mentioned that on the basis of adhering to the traditional architectural features, most of the rural architectural features of Japan still maintain the original form, and the application of building materials is rarely affected by western architectural standards, which is highly humanistic. is feature is also inseparable from the attitude of Japanese rural residents in actively participating in the construction of new villages and controlling the architectural features and forms [18]. On the basis of existing research, this paper proposes to develop and research a digital design platform based on digital computer model, and take parallel robot (Cross IV) as the object.…”
Section: Literature Reviewmentioning
confidence: 99%